Pembentukan Identitas Baru Gen Z melalui Pondok Pesantren Al Fatah Nurul Huda di Nagari Koto Gadang Jaya Kecamatan Kinali Kabupaten Pasaman Barat - Septia Eka Putri; Noor Fadlli Marh (Lembaga Yasin AlSys, 2026)
Although the formation of Generation Z identity in the digital era has been widely studied, research specifically examining the process of forming a new identity through the Islamic boarding school environment from the perspective of Pierre Bourdieu’s theory of social practice remains limited. This study aimed to analyze the process of forming a new identity among Generation Z at Pondok Pesantren Al Fatah Nurul Huda, Koto Gadang Jaya Village, Kinali Subdistrict, West Pasaman Regency. This study employed a qualitative approach with a descriptive case study design. The research informants comprised 19 individuals selected through purposive sampling, including Islamic boarding school administrators, teachers, students, village officials, and members of the surrounding community. Data were collected through observation, in-depth interviews, and documentation and were subsequently analyzed using an interactive analysis model comprising data reduction, data display, and conclusion drawing. The results showed that the formation of a new identity among Generation Z occurred through a continuous habituation process within Islamic boarding school life and resulted in four forms of identity: religious identity, socio-religious identity, Islamic identity, and Islamic social-interaction identity. The formation of these identities occurred through the interaction of habitus, field, and capital, as explained in Pierre Bourdieu’s theory of social practice. These findings broaden the literature on the sociology of Islamic education regarding the role of the Islamic boarding school environment in shaping Generation Z identity. Practically, the findings may serve as a reference for Islamic boarding school administrators, Islamic educational institutions, and parents in strengthening the character development of younger generations through the habituation of religious values. Future research may examine the formation of Generation Z identity across various types of Islamic boarding schools and other Islamic educational contexts. Keywords: Generation Z; Identity Formation; Islamic Boarding School; Pierre Bourdieu; Social Practice